Theoretical Study of the Lasing Output for a Quasi-Three-Level Operation in Nd 3+:YAG Thin- Disk Laser - Ameen, Manahil; Mudhir Shihab Ahmed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
In this research, the effect of each of the concentrations ( Nd+3) was studied (N) the thickness of the thin disk (d) the number of times that the pumping beam passes through the effective medium of this laser (Mp) the reflectivity of the laser output mirror (R 2) The losses of the effective medium (L) and the pumping power used in achieving the reverse qualification (PP) on each of the pumping threshold capacities (Pp.th) and the output power of the laser (Pout) and the efficiency (ŋ) in Nd3+ thin-disk lasers (TDLs) pumping quasi-three-level With continuous operation (cw), at room temperature, and in the Gaussian mode (TEM00), We found under these operating conditions for this laser design that each of the (Pout) and (ŋ) increases by increasing each of (N), (d), (MP), and (R2), while the ( pp.th) decreases with this increase. We also found that as the losses (L) increases (pout) and (ŋ) decrease, and (pp.th) increase, as for increasing the pumping capacity, it leads to an increase in (Pout) only. Both (Pout) and (ŋ) are not affected by such an increase. In light of these results, the typical values for these coefficients were determined, and then you get the highest value for pout and (ŋ) the lowest value for (pp.th) for this laser design under the operating conditions that were adopted in this research.